The analysis demand for animal source food in Indonesia: Using Quadratic Almost Ideal Demand System - Khoiriyah Nikmatul; Anindita Ratya; Hanani Nuhfil; Muhaimin Abdul Wahib (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Indonesia has been experiencing rising animal source food prices during the last five years (decade). In this paper we explore how changes of animal source food prices impact on their demand Indonesia 2016 as expressed in income and price elasticities. Take into account for changes in consumption patterns, as expressed in substitution and complement effects among food items, by including own and cross price elasticities obtained through the parameter estimation of a demand system using QUAIDS. With respect to the total animal food expenditure, chicken meat, beef, fish and milk are luxury goods, while (only) egg is normal goods. The luxuriousness of chicken meat, beef, fish and milk powder decrease with increasing household income level as expressed in quintile level. The results also show that consumers substitute high value commodities such as chicken meat, beef, fishes and powdered milk in case of rising prices with the cheaper and lower preferences. Consequently, households consume a less diversified diet in times of high animal source food prices, focusing their diet on cheaper animal source food commodities. High value animal source foods play an important role in a diversified and nutritionally balanced diet, since they are rich in proteins and essential amino acid. Animal source food 'inflation', which has been led by high value animal agricultural commodities, therefore threatens to worsen the nutritional status of the Indonesian consumer, especially the lower income level.
Keywords: Q18; D11; Q11; Q18; 650; animal source food; consumption-behavior; demand system; urban; rural